2016
DOI: 10.18632/oncotarget.13048
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EZH1 and EZH2 contributes to the suppression of fibrosis-associated genes by miR-214-3p in cardiac myofibroblasts

Abstract: The role of microRNA-214-3p (miR-214-3p) in cardiac fibrosis was not well illustrated. The present study aimed to investigate the expression and potential target of miR-214-3p in angiotensin II (Ang-II)-induced cardiac fibrosis. MiR-214-3p was markedly decreased in the fibrotic myocardium of a mouse Ang-II infusion model, but was upregulated in Ang-II-treated mouse myofibroblasts. Cardiac fibrosis was shown attenuated in Ang-II-infused mice received tail vein injection of miR-214-3p agomir. Consistently, miR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 37 publications
0
31
0
2
Order By: Relevance
“…However, we found that H3K27me3 was reduced but not absent in germ cells, indicating that other histone methyltransferases, such as EZH1, are compensating for EZH2. Previous reports have shown that EZH1 can compensate for the loss of EZH2 in H3K27me3 deposition in a variety of tissues (Shen et al 2008, Bardot et al 2013, Lui et al 2016, Zhu et al 2016, Mu et al 2017. It would therefore be useful to evaluate the role of H3K27me3 deposition in the regulation of spermatogenesis using EZH1/2 singleand double-knockout mice models and to explore this regulatory network using Chip-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that H3K27me3 was reduced but not absent in germ cells, indicating that other histone methyltransferases, such as EZH1, are compensating for EZH2. Previous reports have shown that EZH1 can compensate for the loss of EZH2 in H3K27me3 deposition in a variety of tissues (Shen et al 2008, Bardot et al 2013, Lui et al 2016, Zhu et al 2016, Mu et al 2017. It would therefore be useful to evaluate the role of H3K27me3 deposition in the regulation of spermatogenesis using EZH1/2 singleand double-knockout mice models and to explore this regulatory network using Chip-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that EZH2 is a key factor during cancer progression, including ovarian cancer (Lin et al 2016), prostate cancer (Yang & Yu 2013) and testicular germ-cell tumours (Hinz et al 2010), indicating that EZH2 plays a specific role in germ-cell progression. Furthermore, an increasing amount of evidence suggests that EZH2 is a key regulator of stem cell maintenance and differentiation during ontogenesis in processes including natural killer cell differentiation (Yin et al 2015) and adult hippocampal neurogenesis (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…35, 36 It has also been reported that EZH1 and EZH2 are the targets of miR-214-3p, possibly contributing to cardiac fibrosis. 37 As for miR-342-5p, TGF-β signaling was attenuated by it. 38 However, the relationship between these miRNAs and AF still remains unclear, and we did not determine the functional role of these miRNAs in relation to AF in the present study.…”
Section: Possible Mechanisms Of Novel Mirnas In Relation To Afmentioning
confidence: 97%
“…MiR-214-3p has been reported to be involved in several biological functions and associated with growth, apoptosis, progression and survival. [17][18][19] This shows that miR-214-3p may be a key therapeutic target for miRNA-based therapies for cancer. 23 In addition, HOTAIR also affects the miR-NAs-mediated suppression of target gene expression by competitive binding to miRNAs.…”
Section: ′-Ugacggacagacacggacgaca-5′mentioning
confidence: 98%
“…16 Among these, miR-214-3p has been reported to be associated with growth, progression and survival in cancers. [17][18][19][20] miR-214-3p inhibited proliferation and cell cycle progression by targeting maternal embryonic leucine zipper kinase (MELK), also known as an oncogenic kinase and a key regulator in the malignancy and proliferation of cancer. 21 Induced expression of miR-214-3p in oesophageal cancer cells resulted in a decrease in the expressions of survivin and CUG binding protein 1 (CUG-BP1), an RNA-binding protein, resulting in enhanced sensitivity of oesophageal cancer cells to cisplatin.…”
mentioning
confidence: 99%